2013
DOI: 10.3368/aoj.63.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Patching Compliance with Full-Time vs. Part-Time Occlusion Therapy

Abstract: This study confirms previous reports of similar visual outcomes between PTO and FTO. However, compliance rates for FTO seem to be higher and some children who have failed PTO may improve with FTO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Kane et al ., had compared treatment compliance of continuous occlusion and divided occlusion therapy and had shown the identical increase of visual acuity in both groups (p = 0.82). [ 9 ] This study has shown that increase of visual acuity was not significantly different between both treatments (0.35±0.26 logMar vs 0.38±0.22 logMar; p = 0.72). This is different with the study conducted by Bhoompally et al , whose result was the visual acuity in the group that had received continuous occlusion therapy was better than the group that had received divided occlusion therapy (0.51±0.26 logMar vs 0.59±0.04 logMar; p = 0.27).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Kane et al ., had compared treatment compliance of continuous occlusion and divided occlusion therapy and had shown the identical increase of visual acuity in both groups (p = 0.82). [ 9 ] This study has shown that increase of visual acuity was not significantly different between both treatments (0.35±0.26 logMar vs 0.38±0.22 logMar; p = 0.72). This is different with the study conducted by Bhoompally et al , whose result was the visual acuity in the group that had received continuous occlusion therapy was better than the group that had received divided occlusion therapy (0.51±0.26 logMar vs 0.59±0.04 logMar; p = 0.27).…”
Section: Discussionmentioning
confidence: 76%
“…Evaluated from compliance aspect, Jessica Kane et al . found the compliance in continuous occlusion group to be better compared to divided occlusion group (p = 0.023) [ 9 ]. According to a study conducted by Bhoompally et al .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the results were similar in FTO and PTO group, but compliance was seen better in children in FTO group. They also recommended FTO in children with PTO failure and poor compliance 14. FTO was also considered statistically comparable to PTO in few other studies too 15,16.…”
Section: Discussionmentioning
confidence: 99%